An evaluation of the Quezon City Science High School (QCSHS) library compliance with DECS standards and curriculum requirements - Mabalot, Adalia L.; Aguirre, Vyva Victoria M.; Ramos, Marian S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study was conducted to assess the present condition of the QCSHS Library's compliance with the DECS Standards on the following areas: physical set up, furniture and equipment, collection, personnel/staff and library service. Library collection was further examined to determine if it meets the curriculum needs of a science, mathematics and technology-oriented hugh school. Collection mapping was accomplished based on the RSHS QCSHS curriculum using Loertscher's collection mapping technique along with shelflist count.Integrating the curriculum and the completed collection map gauged, identified and presented the strengths and weakness of the collection.
The study revealed the follwoing: a.)The QCSHS library is not centrally located in the school as it is not accessible to all in the school community, the library is however not free from noise. There is no provision of faculty areas inside the library where they can read, study and prepare lessons; b.) The QCSHS library met the DECS minimum required items and numbers of furniture and equipment tus it can accommodate students for library lesson; c.) Library collection is inadequate to support the school curriculum needs in terms of book number requirement per student as well as currency of resources. Almost 81% of the collection is already outdated and some titles have incomplete volumes. Core, electives and additional subjects in the curriculum do not meet the minimum book requirement per student; d.)General Reference materials have the highest number of book titles in the collection. The rest of the collection per subject area does not meet the required number of books per student under DECS standard. Journal/Magazine subscriptions are irregular. The audio-visual collection is inadequate. Most of the audio-visual materials are in obsolete format and the library has no compatible equipment to view the materials are in obsolete format and the library has no compatible equipment to view the materials thus unable to support the different subject areas in the curriculum. The QCSHS has no existing policy on book evaluation, acquisition, purchase, donation, de-selection and weeding. There is no library committee that will facilitate book evaluation and acquisition. The library staff is insufficient and does not meet the DECS standard for staff requirements in the library.
It is recommended that the following should be taken into consideration: 1.) The library is tied up into the educational functions of the schools in many ways and it requires a functional area. The QCSHS library can be re-located centrally in the school campus to be accessible to everybody. Accessibility to all members of the school community and freedom from noise and other disturbance should be taken in consideration. 2) The library should aim to achieve the equal ratio of furniture and equipment necessary for an increasing number of students especially in support of science and technology requirements of the curriculum. 3) Book requirements should be in equal ratio to the number of students. Purchase of current titles should be undertaken to supersede outdated collection. Another option that must be considered in building the collection is soliciting book donations from alumni,foundation and other libraries. Books that will be purchased and accepted should be current, and its breadth and depth should be looked into: 4) A library committee should be created comprising of the school principal, department heads and the librarian. 5) The QCSHS should hire highly qualified and dynamic full time librarians and support staff so that management and maintenance of the library resources, programs and services can be fully maximized and given to the students and faculty. The librarian's role in curriculum planning and development should be recognized in school. The librarians can contribute meaningfully in planning for library renovation, equipment requisition and book acquisition. The knowledge of materials, resources, techniques, present status of the collection makes the librarian a valuable asset whenever curricular changes are considered and implemented. Continuous active participation of the faculty, school administrator and even the other members of the community should be always encouraged in order to augment the collection.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: High school libraries -- Philippines -- Quezon City -- Evaluation; School libraries -- Philippines -- Quezon City